2011
DOI: 10.1371/journal.pone.0020377
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality of Human Leptospirosis in Reunion Island (Indian Ocean) and Its Association with Meteorological Data

Abstract: BackgroundLeptospirosis is a disease which occurs worldwide but particularly affects tropical areas. Transmission of the disease is dependent on its excretion by reservoir animals and the presence of moist environment which allows the survival of the bacteria.Methods and FindingsA retrospective study was undertaken to describe seasonal patterns of human leptospirosis cases reported by the Centre National de Références des Leptospiroses (CNRL, Pasteur Institute, Paris) between 1998 and 2008, to determine if the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
101
4
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(126 citation statements)
references
References 24 publications
13
101
4
8
Order By: Relevance
“…A study in southern Brazil reported that maximum daily and total monthly rainfalls for the present and previous months were statistically significant predictors of the number of cases of leptospirosis in Poisson regression models [51]. Another study using time series analysis identified a significant correlation between the number of cases in a given month and the associated cumulative rainfall as well as the mean monthly temperature recorded 2 months prior to diagnosis [52]. The study by Robertson et al indicated a 2-month lag in rainfall-case association during the baseline period, but the role of rainfall in the outbreak revealed a more complex relationship [53].…”
Section: Current Status and Future Challengesmentioning
confidence: 99%
“…A study in southern Brazil reported that maximum daily and total monthly rainfalls for the present and previous months were statistically significant predictors of the number of cases of leptospirosis in Poisson regression models [51]. Another study using time series analysis identified a significant correlation between the number of cases in a given month and the associated cumulative rainfall as well as the mean monthly temperature recorded 2 months prior to diagnosis [52]. The study by Robertson et al indicated a 2-month lag in rainfall-case association during the baseline period, but the role of rainfall in the outbreak revealed a more complex relationship [53].…”
Section: Current Status and Future Challengesmentioning
confidence: 99%
“…28 Na África (Ilha da Reunião), os casos de leptospirose tiveram distribuição sazonal e os autores concluíram que dados meteorológicos podem ser utilizados como preditores para a ocorrência da doença, auxiliando na implementação de medidas preventivas. 29 31 Estudos de revisão sistemática, em geral, contribuem para consolidar os achados de diferentes estudos e concluir sobre os fatores associados ao objeto de análise. A diversidade da metodologia, entretanto, pode significar um limitador para a comparação dos resultados encontrados.…”
Section: Aspectos Demográficos E Epidemiológicos Da Leptospiroseunclassified
“…The relationship between meteorological variables and HFRS and leptospirosis has been assessed in many regions [711]. Most studies have focused on the effects of temperature, rainfall, and humidity on the incidences of HFRS and leptospirosis [810, 12, 13].…”
Section: Introductionmentioning
confidence: 99%